The author's guide to murder ebook A novel. - Williams, Beatriz (2024)
"A pure delight from start to finish! Williams, White and Willig are in top form in this clever, engrossing whodunnit with a heart." — Lisa Unger, New York Times bestselling author of The New Couple in 5B Agatha Christie meets Murder, She Wrote in this witty locked room mystery and literary satire by New York Times bestselling team of novelists: Beatriz Williams, Lauren Willig, and Karen White. There's been a sensational murder at historic Castle Kinloch, a gothic fantasy of grey granite on a remote island in the Highlands of Scotland. Literary superstar Brett Saffron Presley has been found dead—under bizarre circumstances—in the castle tower's book-lined study. Years ago, Presley purchased the castle as a showpiece for his brand and to lure paying guests with a taste for writerly glamour. Now it seems, the castle has done him in...or, possibly, one of the castle's guests has. Detective Chief Inspector Euan McIntosh, a local with no love for literary Americans, finds himself with the unenviable task of extracting statements from three American lady novelists. The prime suspects are Kat de Noir, a slinky erotica writer; Cassie Pringle, a Southern mom of six juggling multiple cozy mystery series; and Emma Endicott, a New England blue blood and author of critically acclaimed historical fiction. The women claim to be best friends writing a book together, but the authors' stories about how they know Brett Saffron Presley don't quite line up, and the detective is getting increasingly suspicious. Why did the authors really come to Castle Kinloch? And what really happened the night of the great Kinloch ceilidh, when Brett Saffron Presley skipped the folk dancing for a rendezvous with death? A crafty locked-room mystery, a pointed satire about the literary world, and a tale of unexpected friendship and romance—this novel has it all, as only three bestselling authors can tell it!